Reviews and Responses for Generation of Parametric Climb Trajectories considering Operational Inputs for Aircraft Engine Thrust Extraction - Arts, Emy; Spinielli, Enrico; Bien, Maximilian; Lehmann, Philipp; Friedrichs, Jens (Journal of Open Aviation Science, 2024)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2023.7216